Gamma-ray spectrometry, magnetic and gravity signatures of Archean nuclei of the Borborema Province, Northeastern Brazil - OLIVEIRA, Roberto Gusmão de (2024)
Gamma-ray spectrometry, as well as magnetic and gravity data, are used to investigate the geophysical signatures of the Archean nuclei of the Borborema Province. Natural radioactivity, magnetic anomalies, and residual Bouguer gravity anomalies of the Archean nuclei exhibit distinct signatures in relation to adjacent Proterozoic domains. Gamma-ray spectrometry data reveal eTh enrichment in relation to K and eU contents in Archean units. Assuming that K and U were the dominant isotopes, this relative enrichment of eTh can be explained by the fact that Th radioisotopes have a longer half-life than the other two radionuclides and that 4.56 Ga has elapsed since Earth's formation. The intensity of the total magnetic gradient in Archean units is greater than in Proterozoic units in most nuclei. The Archean units underwent deformation and metamorphism in the Brasiliano/Pan-African Orogeny; therefore, the magnetic characteristics now observed in Archean mafic-ultramafic rocks, iron formations and gneiss-migmatite complexes are the joint result of their primary properties and the superposed effects of the orogeny. All Archean nuclei of the Borborema Province show positive residual Bouguer gravity anomalies. This could be due to the conservation of the main petrophysical properties of the Archean lithosphere, and their preservation during the intense granitization that occurred in the Brasiliano/Pan-African Orogeny. As magnetic and gravity methods provide information from depth, it is possible to infer the continuity of some Archean nuclei beyond the limits established by surface geological data. Based on these results, it will be possible to use geophysical signatures to investigate the possible existence of unknown Archean units in the province.